EFFECT OF NUTRITIONAL AND PROCESS PARAMETERS ON PRODUCTION OF COPOLYMER, POLY (HYDROXYBUTYRATE-CO-HYDROXYVALERATE) BY HALOMONAS CAMPISALIS MCM B-1027 AS ASSESSED USING TAGUCHI DESIGN OF EXPERIMENTS - S.O. KULKARNI; P. P. KANEKAR; J.M. RAJWADE (International Journal of Pharma and Bio Sciences, 2014)
Polyhydroxyalkanoates (PHAs) are a group of microbial biodegradable polymers having potential to replace synthetic plastics. Several factors are known to influence PHA biosynthesis e.g., bacterial strain used, carbon and nitrogen sources provided, culture conditions, etc. These factors interact with each other during productionand their interaction can be assessed using statistical methods. In the present study, Taguchi Design of Experiments is performed to find out the effect of six different factors viz. incubation period, medium: flask volume ratio, pH of production medium, concentration of maltose, yeast extract and sodium chloride at three levels on production of PHA with 18 well defined experiments (L18 Orthogonal Array). The data obtained was analyzed statistically and it was found that incubation period was the most significant factor contributing 28.84% to PHA production while concentration of maltose was found to be the least significant (1.81%) in the PHA production.